318 Effect of Initial Providing Time of Oat Hay on Performance, Health, Behavior and Rumen Fermentation in Calves. (8th October 2021) - Chen, Tianyu; Xiao, Jianxin; Li, Tingting; Ma, Jing; Cao, Zhijun
Abstract: To determine the appropriate time to feed hay to calves, 210 healthy Holstein calves at d 2 were randomly divided into 3 groups: feeding basic diet (starter) without hay (CON), inclusion of oat hay from the second week (H2) or fourth week (H4) in addition to the basic diet. All calves were weaned on d 56 and raised in the same hutches until the end of the experiment (d 70). Calf starter intake and fecal score were recorded daily throughout the experimental period. Body weight, body size, blood and rumen fluid samples were collected every 2 weeks before weaning and once a week after weaning. Inclusion of oat hay in the basic diet (H2 and H4) resulted in increased body weight (P < 0.01) and average daily gain (P < 0.01) throughout the experiment when compared to the basic diet (CON) only. Calves fed oat hay from 2 weeks of life had the highest starter intake (P < 0.01), average daily gain (P < 0.01) in the pre- and post-weaning periods. Body length and heart girth was similar between treatments. The H2 calves had lower diarrhea frequency (P < 0.05) and diarrhea days (P < 0.05) during the post-weaning period. Compared to the CON calves, inclusion of hay increased the rumen pH (P < 0.01), while decreasing the NH3 -N (P < 0.01) and tend to decrease the total VFA (P < 0.06) during the entire trial. Calves in H2 treatment spent more time ruminating (P < 0.01), but less time standing (P < 0.05), eating starter (P < 0.01) and engaging in abnormal behaviors (P < 0.01). In conclusion, calves supplemented with oat hay improved growth rate and rumen fermentation when compared with calves fed only starter, and adding hay from 2 weeks of calves life may be the best choice for the farm to have the greatest growth and health performance.